Lavrentivs Ramævs Præfect. Amercvr. S. Cæs. Mai. A Consil. Bellic. Dvctor XIII. Tvrmar. Eqvit. Lev. Armat. Sereniss. Leopoldi Archidvc. Avstriæ etc. Consiliar. Et Cvbicvlar - Kilian, Lucas (1611)
Österreichischer Generalobrist und Söldnerführer